Le musée municipal de l’Hygiène et sa genèse administrative. Contribution à une histoire des musées techniques municipaux à Paris - Miriam Simon (In Situ)
In order to draw attention to its technical accomplishments and its capacities for innovation, the Parisian municipal administration presented its achievements at several universal exhibitions during the Third Republic. This was a period of considerable modernisation of the city, in pursuance of the work begun under Haussmann during the Second Empire. Following these exhibitions, the city opened ‘professional museums’, with the aim of promoting its initiatives in fields such as hygiene and public health and providing training for its employees. These places were open to the public. This article offers a survey of the present-day situation in Paris and examines the first technical museums created in the city. Its analysis of the efforts undertaken here by the city administration give us a better understanding of how the municipal museum of hygiene came into existence within the administration. This museum is the ancestor of the visits organised today to the Paris sewer system.